The evolutionary fate of MULE-mediated duplications of host gene fragments in rice - Juretic, Nikoleta; Hoen, Douglas R.; Huynh, Michael L.; Harrison, Paul M.; Bureau, Thomas E. (Genome Research, 2005)
DNA transposons are known to frequently capture duplicated fragments of host genes. The evolutionary impact of this phenomenon depends on how frequently the fragments retain protein-coding function as opposed to becoming pseudogenes. Gene fragment duplication by Mutator-like elements (MULEs) has previously been documented in maize, Arabidopsis, and rice. Here we present a rigorous genome-wide analysis of MULEs in the model plant Oryza sativa (domesticated rice). We identify 8274 MULEs with intact termini and target-site duplications (TSDs) and show that 1337 of them contain duplicated host gene fragments. Through a detailed examination of the 5% of duplicated gene fragments that are transcribed, we demonstrate that virtually all cases contain pseudogenic features such as fragmented conserved protein domains, frameshifts, and premature stop codons. In addition, we show that the distribution of the ratio of nonsynonymous to synonymous amino acid substitution rates for the duplications agrees with the expected distribution for pseudogenes. We conclude that MULE-mediated host gene duplication results in the formation of pseudogenes, not novel functional protein-coding genes; however, the transcribed duplications possess characteristics consistent with a potential role in the regulation of host gene expression.